2017
DOI: 10.1111/anu.12529
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid: A natural compound as an efficient feed additive for GIFT (Oreochromis niloticus)

Abstract: This study aimed to investigate the effect of dietary ferulic acid (FA) supplementation on growth performance, antioxidant capacity and some physical characteristics of flesh in genetic improvement of farmed tilapia (GIFT) juveniles. Five diets supplemented with 0, 50, 100, 200 and 400 mg/kg FA were prepared. Weight gain was significantly increased, while feed conversion ratio, viscerosomatic index and hepatosomatic index were significantly decreased in fish fed FA diet at 100 mg/kg feed (p < .05). FA suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
5
18
0
Order By: Relevance
“…The downward trend or the significant reduction of the serum ALB, TP and ALP value in the oxidized fish oil‐supplemented groups suggested a weaker non‐specific immune response of the fish. The enhancement of the serum ALB, TP and ALP in the fish exposed to FA indicated that FA might have stimulated the innate immune responses in tilapia, which was consistent with our previous result (Yu et al., 2018). Moreover, no significant difference existed in the ALB and ALP value in group F and group OF + FA, and the TP value in group OF + FA was higher than that in group F, indicating the addition of FA almost neutralized the negative effects of the oxidized fish oil.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The downward trend or the significant reduction of the serum ALB, TP and ALP value in the oxidized fish oil‐supplemented groups suggested a weaker non‐specific immune response of the fish. The enhancement of the serum ALB, TP and ALP in the fish exposed to FA indicated that FA might have stimulated the innate immune responses in tilapia, which was consistent with our previous result (Yu et al., 2018). Moreover, no significant difference existed in the ALB and ALP value in group F and group OF + FA, and the TP value in group OF + FA was higher than that in group F, indicating the addition of FA almost neutralized the negative effects of the oxidized fish oil.…”
Section: Discussionsupporting
confidence: 92%
“… The formulation of vitamin and mineral premix was the same as the previous experiment (Yu et al., 2018). …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the dietary inclusion of 10 to 15 g/kg of Roselle calyx extract, containing cyanidin, delphinidin, synergenic acid and ellagic acid as the most abundant PCs, enhanced growth performance and FI in Nile tilapia (El-Mesallamy et al, 2016). These results are consistent with a study by Yu et al (2017) that also reported an increase in growth performance of tilapia juveniles fed with supplemented diets with 100 mg/ kg of ferulic acid. These data indicate that the effect of PCs on growth performance and FI might depend on their inclusion level and the difference in their phenolic profiles, as well as, the fish species and the species' feed preferences.…”
Section: Growth Performance Feed Intake Feed Efficiency and Survivalsupporting
confidence: 93%
“…Vitamin E concentrations in diets and livers were measured by using the HPLC method as described by Tangney (Tangney et al, ). Activities of the serum total superoxide dismutase (SOD) and the catalase (CAT) along with the content of the serum malondialdehyde (MDA) were analysed by colorimetry using the Diagnostic Reagent Kits from Nanjing Jiancheng Bioengineering Institute (China; Aebi, ; Beuge & Aust, ; McCord & Fridovich, ; Yu et al, ). All analyses were conducted in triplicate.…”
Section: Methodsmentioning
confidence: 99%